Perceived Organizational Support: A Case of Special Education Teacher - Fadhilah Ramadhani (UNUSA Press, 2020)
This study aims to examine perceived organizational support within special education teacher in Surabaya. Special education needs a lot more attention because some inclusive system in public schools are not well developed which affecting the teachers’ well being. This study starts with a literature review building the knowledge basis for the topic. The primary data was gathered through several interviews with shadow teachers to look into the difficulty which resulted in lack of perceived organizational support among special education teachers. The perceived organizational support in teachers was examined through the three beneficialfactors for POS, namely: fairness, supervisor support, and organizational rewards and job conditions. Result shows that the organisation still need to improve the three beneficial factors for POS so that the teachers can feel more supported by the organisation.